Princípios do sigilo e da publicidade processual : colisão aparente entre os arts. 5º, X e 93, IX da Constituição Federal - Silva, Donato Henrique da (2010)
The contemporary society seems to have easily adapted to the changes in its daily relationships and, consequently assimilated, without resistances, the needs to live together with the new phenomena imposed by those transformations that ended demanding the whole society compromising, including the State, the respect to rights and warranties insured by the Federal Constitution. The intimacy protection consecrated by the 5th art., X, of the Great Letter of 1988, is one of those warranties that seems to have conquered the unanimity. The right of being alone, the respected of the privacy, immaterial goods as the dignity, the honor and the personality ended has become a previous condition for the individual to maintain a relative harmony in the social living. Happens that other normative dispositions are also considered imperative for the configuration of the democratic State of Right, among them, the warranty of publicity, the necessity of transparency in the accomplishment of the acts to the constituted Powers of the Republic, within the Judiciary is also included when it offers juridical services. However, that constitutional warranty foreseen in the art. 93, IX, of CF/88 receives critics on the part of the doctrine, under the support that in spite of the constitutional text to treat the publicity of the judicial acts as a rule, it also says, in an ambiguous way, that those same acts can be practiced behind closed doors, or in a secret way, limiting the knowledge to the involved parts and their lawyers. This way, a supposed contradiction is verified among principles, which should prevail being verified the concrete case of the beginnings: What does treat the protection of the individuals' intimacy or what does the one impose publicity to all the procedural acts, in consonance with the public interest? Therefore, it is those difficulty questionings that tries to be clear in the present work, concluding at the end into contradiction situations among principles, must the interpreter take into consideration judges of good sense and reasonably aim to the solution for the removal of one of them